The TK0271 Protein Activates Transcription of Aromatic Amino Acid Biosynthesis Genes in the Hyperthermophilic Archaeon Thermococcus kodakarensis - Yasuyuki Yamamoto (American Society for Microbiology, 2019)
ABSTRACT TrpY from Methanothermobacter thermautotrophicus is a regulator that inhibits transcription of the Trp biosynthesis (trp) operon. Here, we show that the TrpY homolog in Thermococcus kodakarensis is not involved in such regulation. There are 87 genes on the T. kodakarensis genome predicted to encode transcriptional regulators (TRs). By screening for TRs that specifically bind to the promoter of the trp operon of T. kodakarensis, we identified TK0271. The gene resides in the aro operon, responsible for the biosynthesis of chorismate, a precursor for Trp, Tyr, and Phe. TK0271 was expressed in Escherichia coli, and the protein, here designated Tar (Thermococcales aromatic amino acid regulator), was purified. Tar specifically bound to the trp promoter with a dissociation constant (Kd) value of approximately 5 nM. Tar also bound to the promoters of the Tyr/Phe biosynthesis (tyr-phe) and aro operons. The protein recognized a palindromic sequence (TGGACA-N8-TGTCCA) conserved in these promoters. In vitro transcription assays indicated that Tar activates transcription from all three promoters. We cultivated T. kodakarensis in amino acid-based medium and found that transcript levels of the trp, tyr-phe, and aro operons increased in the absence of Trp, Tyr, or Phe. We further constructed a TK0271 gene disruption strain (ΔTK0271). Growth of ΔTK0271 was similar to that of the host strain in medium including Trp, Tyr, and Phe but was significantly impaired in the absence of any one of these amino acids. The results suggest that Tar is responsible for the transcriptional activation of aromatic amino acid biosynthesis genes in T. kodakarensis. IMPORTANCE The mechanisms of transcriptional regulation in archaea are still poorly understood. In this study, we identified a transcriptional regulator in the hyperthermophilic archaeon Thermococcus kodakarensis that activates the transcription of three operons involved in the biosynthesis of aromatic amino acids. The study represents one of only a few that identifies a regulator in Archaea that activates transcription. The results also imply that transcriptional regulation of genes with the same function is carried out by diverse mechanisms in the archaea, depending on the lineage.